Rectal polyposis as a guide to duodenal polyposis in familial adenomatous polyposis. - Spigelman, A D (1992)
Almost all patients with familial adenomatous polyposis (FAP) develop duodenal polyps, the severity of which is graded stage 1 (minor) to stage V (cancer). Regular endoscopy is recommended for all patients with FAP. To test whether the development of severe duodenal polyposis could be predicted in another way, rectal and duodenal polyp severity were compared in 91 patients with FAP. The fulguration ratio (number of rectal fulgurations divided by number of years since colectomy) supplied the rectal polyp severity index. Patients with stage V duodenal polyposis had significantly higher fulguration ratios (median 0.38) than did patients with stage 1 disease (median 0; P = 0.009). However, the wide scatter of results means that rectal polyp severity cannot be used as a guide to duodenal polyp severity in individual patients. The coexistence of populations with severe duodenal and rectal polyposis suggests that environmental factors are important in phenotypic expression in FAP.